Frequency of deletion of CDKN2A (9p21) gene in T-cell lymphomas in FISH analysis - Pastwińska, Anna; Rygier, Jolanta; Woroniecka, Renata; Grygalewicz, Beata; Krawczyk, Paulina; Pieńkowska-Grela, Barbara; Rymkiewicz, Grzegorz; Feliksbrot-Bratosiewicz, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Cytogenetic investigations play an important role in the diagnosis of lymphomas. One of the recurrent aberrations in T-cell non-Hodgkin lymphoma (T-NHL) is a loss of the suppressor gene CDKN2A (9p21). The loss of this region is not seen in the karyotype; this deletion is submicroscopic in most cases. Material and methods : We present the results of the status of 9p21 deletion with the CDKN2A gene in 55 patients with cases of T-NHL, which were investigated in our laboratory in 2007-2010. We use FISH with a unique probe, CDKN2A/CEP9, for the 9p21 region on material obtained mostly by fine needle aspiration biopsy (FNAB) of lymph nodes or extranodal tumours, cerebrospinal, pleural and peritoneal fluids, or peripheral blood and bone marrow. Results : Deletion of 9p21 was found in 29% (n = 55) of patients with T-NHL. Loss of CDKN2A was observed in 11 (55%) out of 20 cases with T-LBL/ALL, in 2 (33%) out of 6 with T-LGL and in 3 (20%) out of 15 patients with peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS). Patients with MF, SS, primary cutaneous peripheral T-cell lymphomas and other sporadic subtypes of peripheral T-cell lymphomas did not show deletion of this region. In studied lymphomas with deletion we observed a heterogeneous signal pattern in most cases (over 81%). Analysis of the signal pattern of CDKN2A deletion showed clones with mono- and biallelic deletion in cells with variable ploidy. Probably, this phenomenon is related to concurrent incidence of cells which are in different stages of neoplastic transformation.